Implementing sustainability in small and medium-sized construction firms: The role of absorptive capacity. Issue 4 (18th July 2016) - Upstill-Goddard, James; Glass, Jacqui; Dainty, Andrew; Nicholson, Ian
Abstract : Purpose: – Construction organisations are becoming increasingly aware of the impacts of their operations, from both an environmental and, more recently, a social viewpoint. Sustainability standards can enable an organisation to evidence a benchmarked level of performance against a particular issue. To date, research on standards has largely focused on the operational and administrative aspects of their enactment, rather than how they might affect – and be appropriated by – organisational actors. The purpose of this paper is to examine how capacity for learning can affect the success of implementing standards within two construction SMEs. Design/methodology/approach: – Taking an organisational learning and absorptive capacity (ACAP) perspective, this research uses the case study approach and abductive logic to understand what role learning plays with regard to sustainability standard implementation. Findings: – The results reveal that strong communication channels and commitment to training programmes increase the capacity for implementing standards, but that SMEs tend only to approach standards if they see immediate financial benefits stemming from their implementation. Practical implications: – SMEs provide a challenging context for the implementation of sustainability standards unless there are significant external levers and extrinsic motivation for them to be embraced. Care should be taken in incorporating these aspects into the future design of standards that are more aligned with SME needs. Social implications: – Stakeholders should seek to apply pressure to firms to positively influence engagement with sustainability standards. Originality/value: – The role and importance of ACAP is an underdeveloped debate in the certification field. This study is the first that links the process of implementing a standard with the ACAP of an organisation.